A systematic review on advances and perspectives of image compression in telemedicine. (2015) - Sophia, P. Eben; Anitha, J.
Transmission of medical images from one place to another is an important part of telemedicine applications. Raw medical images take huge time for transmission which makes telemedicine process tedious and impractical. When subjected to compression either there will be a loss of data or size will not be reduced much. One way to overcome this problem is to allow some loss of data so that the size is reduced and also diagnostically important parts remains unaffected. This is the process behind region-based compression. Critical analysis has been done on the advances in the compression techniques developed till now and their perspectives in the field of telemedicine. Emphasis is laid on region-based compression a technique which paves the way for efficient and effective compression of medical images. The review also covers the scope of future research along with suitable solution to improve the performance of compression algorithms for telemedicine.